Return to Play, Performance, and Economic Analysis of National Football League Players After Lisfranc Injury. Issue 4 (6th April 2023) - Abed, Varag; Fine, Rebecca; Fine, Rachel; Hawk, Gregory S.; Conley, Caitlin; Jacobs, Cale; Stone, Austin V.
Background: A Lisfranc injury can occur to either the ligament or bone, which causes instability when attempting to perform strength and balance maneuvers. Purpose/Hypothesis: The study's aims were to (1) analyze the return-to-play (RTP) rate and performance level of players in the National Football League (NFL) after Lisfranc injury and (2) determine the economic and financial impact of Lisfranc injuries to the NFL. We hypothesized that there would be a low RTP rate following Lisfranc injury in the NFL. Study Design: Case series; Level of evidence, 4. Methods: Multiple online public records were used to identify NFL players with Lisfranc injuries between the 2009 and 2020 seasons. Players were assessed according to their RTP statistics: snap count, approximate value (AV), games played, and games started. Nonparametric methods were used to compare player statistics before and after injury. Also, player salaries while injured were calculated (in 2022 US dollars after adjusting for inflation) to approximate economic loss for those players who returned to play. Results: A total of 33 NFL athletes sustained a Lisfranc injury during the study period. Most Lisfranc injuries were experienced by offensive linemen (n = 8; 24.2%), followed by running backs (n = 7; 21.2%). Overall 27 players (81.8%) returned to play after injury at a median of 11.0 months (IQR, 10.2-11.8 months). There were no significant differences between pre- and postinjury snap counts or number of games played and started. In terms of player performance, there was a statistically significant decrease in AV at 1 year postinjury (median [IQR], 6.0 [4.0-10.0] preinjury vs 5.0 [2.5-7.5] postinjury; P = .022). The overall cost of recovery amounted to $104.7 million, with quarterbacks (n = 4) accounting for the greatest cost at $32.6 million. The next 2 most expensive positions were offensive and defensive linemen (n = 5 each) at $19.4 million each. Conclusion: Our results did not support the hypothesis, as the RTP rate for NFL athletes sustaining Lisfranc injuries was 81.8%. This injury was associated with a significant decrease in AV 1 year postinjury. In terms of economic impact, quarterbacks accounted for almost one-third of expenses while constituting only 14.8% of injuries.